IMPLEMENTATION OF TEAM QUIZ STRATEGY TO IMPROVE ARABIC VOCABULARY OF FIFTH GRADE STUDENTS OF MI RAUDLATUS SYUBBAN (Al-Hasani: Journal of Islamic Studies, 2025)
Vocabulary mastery is one of the important requirements in achieving the four basic Arabic language skills, namely listening,  speaking, reading, and writing. This study aims to analyze the implementation of the Team Quiz strategy in improving the mastery of Arabic vocabulary of fifth grade students of MI Raudlatus Syubban Wegil Sukolilo Pati. The research method used is classroom action research (CAR) which was carried out in two cycles. The research subjects were 17 students who were also used as samples. The results of the study showed that students' vocabulary mastery before the implementation of the Team Quiz strategy was still relatively low, with an average class score of 58.82; only 3 students achieved completeness, while 14 students had not yet completed it. After the implementation of the Team Quiz strategy in cycle I, there was an increase in vocabulary mastery with an average score of 72.35, although this achievement was still within the minimum limit of the Arabic KKM, which was 70. Therefore, the research was continued to cycle II. In cycle II, students' vocabulary mastery experienced a significant increase with an average score reaching 89.41 and all students were declared to have completed the learning. This increase in learning outcomes was supported by observation data on teacher and student activities, where the teacher's observation score increased from 77.27 in cycle I to 84.09 in cycle II, while the student's observation score increased from 70.83 in cycle I to 89.41 in cycle II. Based on these results, it can be concluded that the implementation of the Team Quiz strategy is effective in improving students' mastery of Arabic vocabulary in grade V of MI Raudlatus Syubban.